P5.079 Laboratory Diagnosis of Neurosyphilis in Patients Co-Infected with Human Immunodeficiency Virus (HIV) and Negative-HIV Patients in Montevideo-Uruguay. (13th July 2013) - Balleste, R; Rodriguez, N; Garcia, N; Lopez, P; Buzzi, C
Abstract : Background: Syphilis laboratory diagnosis, is made through the dosage of circulating antibodies in blood, but is not enough when neurological involvement is suspected. A positive Venereal Disease Research Laboratory test (VDRL) result in cerebrospinal fluid (CSF) establishes the diagnosis of neurosyphilis, but it´s negativity does not rule it out, therefore the need to use other immunological tests arises. The aim of our study was to evaluate the immunological tests performance used for neurosyphilis diagnosis and compare them between HIV infected and uninfected patients. Methods: We studied 37 patients (17 positive HIV and 20 negative HIV) from 2005 to 2012. We selected patients with positive Treponema Pallidum Hemagglutination Assay (TPHA) result in serum and CSF. Those patients underwent VDRL and, IgG and Albumin dosage in serum and CSF. TPHA-index and ITpA-index were calculated, intrathecal IgG production and indemnity of the blood brain barrier were evaluated through "Reiber´s" diagram. Results:Neurosyphilis was diagnosed in 21 patients (6 positive HIV and 15 negative HIV): 18 reactive CSF VDRL, 13 TPHA in CSF > 1/320, 13 Index TPHA/Albumin > 70, 24 ITpA index ≥ 2, in 3 patients neurosyphilis diagnosis was established only by high TPHA titers and high TPHA-index (2 positive HIV and 1 negative HIV).14 patients had Intrathecal IgG synthesis and 10 had blood-brain barrier disruption. Conclusions: CSF VDRL made neurosyphilis diagnosis in 86% of patients, with a high concordance between CSF VDRL and CSF TPHA titer > 1/320 and TPHA-index > 70; the immunological tests performance was similar in HIV positive and HIV negative patients. Neurosyphilis diagnosis was established with the CSF/serum indexes and TPHA titers in 14% of the studied population. This highlights the importance of including the indexes in the routine diagnosis of neurosyphilis. Intrathecal IgG synthesis and disruption of the blood-brain barrier predominated in patients with neurosyphilis.